Cinema of Confinement - Connelly, Thomas J., 1971- (Book collections on Project MUSE., 2019)
"In this book, Thomas J. Connelly draws on a number of key psychoanalytic concepts from the works of Jacques Lacan, Slavoj Žižek, Joan Copjec, Michel Chion, and Todd McGowan to identify and describe a genre of cinema characterized by spatial confinement. Examining classic films such as Alfred Hitchcock's Rope and Stanley Kubrick's The Shining, as well as current films such as Room, Green Room, and 10 Cloverfield Lane, Connelly shows that the source of enjoyment of confined spaces lies in the viewer's relationship to excess. Cinema of Confinement offers rich insights into the appeal of constricted filmic spaces at a time when one can easily traverse spatial boundaries within the virtual reality of cyberspace."